Birth order or screen time: what strongly predicts executive function skills development in preschool children? - Chichinina, Elena; Almazova, Olga; Veraksa, Nikolay (Frontiers in Education, 2025)
The majority of screen time recommendations differ among parents of toddlers, preschoolers, and schoolchildren. In families with more than one child, it becomes more difficult for parents to apply these recommendations to each child individually because of the age difference between siblings. Currently, how screen time is affected by the birth order has been poorly studied. Therefore, this study aims to investigate birth order and screen time as predictors of executive function skills development. Executive function skills were assessed in children at two different stages: when they were 5–6 years old and again 1 year later. The study sample consisted of 271 children (51% boys) from two-child families. Half of the participants were first-born children, while the other half were second-born children. The age difference between the siblings was not more than 5 years. Of all executive function skills, only the development of verbal working memory over a year was predicted by the birth order. Specifically, the development of verbal working memory over a year in 5–6-year-old second-born children was less than that in 5–6-year-old first-born children. Active screen time and passive screen time were not predictors of executive function skills development. In addition, it was found that second-born preschool children were exposed to more active screen time than first-born children. Based on the results obtained, in two-child families with children aged 5–6 years, being second-born may be less beneficial for the development of verbal working memory development than being first-born. Therefore, parents of second-born preschool children should be especially careful in adhering to screen time recommendations.